PENGARUH MOTIVASI DAN IKLIM PSIKOLOGIS TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK MADYA PEKANBARU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Mianto, Astris; Hendriani, Susi; Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine and analyze the influence betweenMotivation and Psycological Climate, on the Employee Performance of KantorPelayanan Pajak Madya Pekanbaru With Job Satisfaction As InterveningVariables. The population of this study were employee in Kantor Pelayanan PajakMadya Pekanbaru with the all level who totaled 95 people. The sample in thisstudy were 95 people obtained by the method of Stratified Random Sampling. Theinstrument used for data collection is by ordinal scale model questionaire. To testthe hypothesis used descriptive analysis and path analysis. The results of dataanalysis show that (1) Motivation has a positif and significant effect onPerformance, (2) Psycological Climate has a positif and signifikant effect onPerformance (3) Job Satisfaction has a positif and significant effect onPerformance (4) Motivation has a positif and significant effect on Performancewith Job Satisfaction As Intervening Variables (5) Psycological Climate has apositif and significant effect on Performance with Job Satisfaction AsIntervening Variables.